BUILDING A STRONG RELIGIOUS UNDERSTANDING: THE ROLE OF CONSTRUCTIVIST THEORY IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Ifa Datuzuhriah; Muhammad hasby; Ermis Suryana; Kurratul ‘Aini (SOSIOEDUKASI, 2026)
This article aims to analyze the implementation of constructivist theory in Islamic Religious Education (PAI) learning as an effort to enhance students’ religious understanding in a solid and contextually relevant manner in line with contemporary developments. PAI learning that is still dominated by traditional, teacher-centered methods is considered less effective in fostering deep understanding and students’ critical thinking skills. Therefore, constructivist theory is proposed as an alternative approach that emphasizes the active role of learners in constructing knowledge through learning experiences, social interaction, and reflection. This study employs a qualitative approach with a case study design conducted at SD Negeri 02 Lubuk Keliat. The research informants consist of an Islamic Religious Education teacher and sixth-grade students. Data were collected through classroom observations, in-depth interviews, and analysis of instructional documents. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the implementation of a constructivist approach through group discussions, case studies, learning simulations, and the integration of educational technology enhances students’ learning motivation, understanding of religious subject matter, critical thinking skills, and learner autonomy. Nevertheless, the implementation of constructivism faces several challenges, including limited facilities and infrastructure as well as differences in students’ academic abilities. To address these challenges, teachers apply differentiated instruction strategies and strengthen collaboration between teachers and students. Based on the research findings, it can be concluded that constructivist theory is an effective approach in Islamic Religious Education learning and contributes positively to shaping students who possess a deeper, more critical, and more applicable understanding of religion in their daily lives.